Fullerenes and Relative Materials Properties and Applications - Kamanina, Natalia V. (IntechOpen, 2018)
In the period of rapid and intensive development of general electronics, this book entitled Fullerenes and Relative Materials - Properties and Applications is quite systematic and useful. It considers some aspects on synthesis, structural, vibrational, tribology, and optical properties of the fullerenes and relative materials. Some parts of the book present the specific area of the applications of the studied nanostructures. The book contains eight chapters. The special approach and interesting results on the unique properties of the materials studied as well as the different areas of their applications in general optoelectronics, solar energy and gas storage, laser and display, and biomedicine are shown. It is important for education process and for the civil and special device operations.